Strategi Pemasaran Produk Mainan Anak-Anak dari Limbah Kayu PT Safira Tumbuh Berkembang - Naomi Dongoran; Ma'mun Sarma; Budi Suharjo (Institut Pertanian Bogor, 2015)
After year such a natural resources as wood becomes rare, so its use needs to be to the most efficient way, in line with it, wooden waste use becomes important. One of the companies which processes and makes use of the wooden waste to be children toys of economical value in Bogor is PT Safira Tumbuh Berkembang (PT STB). The research objectives are (1) to identify factors that influence a consumer’s decision making, and (2) to set a recommended marketing strategy to develop the business. The population In this research is students’ parents and teachers of 10 kindergartens in the City of Bogor. Samples were determined by purposive sampling, with consideration of easily accessible and the TK is willing to be interviewed. From each kindergarten a sample of 6 respondents comprising 3 parents and 3 teachers is taken, in order to make the total number of respondents of regarding 60 people. Data analysis method used is Thurstone, with consideration of a study conducted to explore consumer behavior in decision making. From the above analysis, the marketing strategy to do are as follows: (1) to lower the price of 9.34% of the set price, (2) To improve a new design in accordance with educational content element and bright colors combination on the toy, (3) to maintain the quality in accordance with the market segment, (4) maintain and develop the educational element content and a combination of bright colors found in children's toys as unique or characteristic of the designs produced by PT STB, (5) To develop promotion through direct interaction between sellers and the targets (personal selling) in a potential kindergarten as well as (6) To develop selling points through cooperation with children toy stores in malls/shopping centers